The need preservation of books in libraries : the environment - Skaik, Huda; Hassan, Basri; Wan Mamat, Wan Ali (IIUM Press, 2011)
Books and other library materials should not be seen as physical items shelved on the stacks, they should be regarded more for the important information they contain, and how useful this information is for users seeking to satisfy their needs or passion for reading these materials. However, these materials should be regarded as objects governed by the same laws that affect all organic materials (Harvey, 1993). This probably justifies why some preservation administrators request that library science education should have a compulsory course about preservation to help all librarians understand the value of the items they deal with on a daily basis. Deterioration is a change of original state of any material by interaction between the object and the factors of destruction. The different types of deterioration are reflected in wear and tear, shrinkage, cracks, brittleness, distortion, bio infestation, discoloration, abrasion, hole, dust and dirt accumulation, etc. Deterioration as a loss of quality in any library material that decreases its ability to carry out its intended function. Generally, deterioration results from a number of variant factors classified into two main categories; inherent and external. Such categories include environmental, human, biological, chemical and natural. For purposes of this study, concern will be addressed to environmental and human factors only.